ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI PUSKESMAS KEMARAYA KECAMATAN KENDARI BARAT KOTA KENDARI - Alfira Rezky Fajriati Rahmad; Adrian Tawai; Suhadi (Journal Publicuho, 2023)
This survey was conducted to measure the services of Kemaraya Health Center, West Kendari District, Kendari City through the Community Satisfaction Index. This quantitative descriptive study will present the results of research using most numerical statements and narrative sentences with qualitative explanatory forms. The study will be conducted at Kemaraya Health Center, West Kendari District, Kendari City from August 2022 to October 2022. The sampling technique uses the Likert scale most commonly used in survey research. The data collection techniques used are questionnaires, notes, and observations. The Community Satisfaction Index of Kemaraya Health Center in Kendari City falls into the good category with a magnitude of 81.76. Based on the nine performance elements, executive capital is the element with the highest index value of 84.75 and is therefore at a good level. While the indicator with the lowest index value, namely the infrastructure indicator 76.5.